Experimental Investigation of the Size Effect of the Mode I Static Fracture Toughness of Limestone - Sheng Zhang; Longfei Wang; Mingzhong Gao (Advances in Civil Engineering)
To study the size effect of the fracture toughness of notched semicircular bend (NSCB) specimens, the dimensionless energy release rate equation of the NSCB specimen was deduced on the basis of the Bažant energy release rate. The influence of the crack length and the specimen size on the fracture toughness was analyzed. The Bažant scale equation was obtained using the International Union of Laboratories and Experts in Construction Materials, Systems, and Structures (RILEM) method. Finally, the Bažant equation was used to analyze the fracture toughness of an NSCB specimen with a radius of 75 mm, and the degree of variation was predicted. The results show that a longer fracture is correlated with a lower fracture toughness value for the same sample size and that a larger specimen radius is correlated with a higher fracture toughness value for the same crack length. The obtained Bažant equation correctly reflects the scale law of the fracture toughness of the NSCB specimen and provides highly accurate predictions of the fracture toughness of large specimens, with an error of not more than 3%. The results obtained in this study provide a new reference method and theoretical basis for the future testing work.